2020
DOI: 10.3390/plants9050631
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gene Isoforms Related to Cellulose and Lignin Biosynthesis in Kenaf (Hibiscus cannabinus L.) Mutant

Abstract: Kenaf is a source of fiber and a bioenergy crop that is considered to be a third world crop. Recently, a new kenaf cultivar, "Jangdae," was developed by gamma irradiation. It exhibited distinguishable characteristics such as higher biomass, higher seed yield, and earlier flowering than the wild type. We sequenced and analyzed the transcriptome of apical leaf and stem using Pacific Biosciences single-molecule long-read isoform sequencing platform. De novo assembly yielded 26,822 full-length transcripts with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Despite the advantages of long-read sequencing, developing unified and practical approaches to analyzing the data remains a significant challenge. Previous studies applied standard Iso-seq bioinformatic pipelines to generate high-quality isoforms 34 , 35 . In the current study, we modified the standard pipeline by incorporating the Cogent tool 36 and the Cupcake ToFU package to refine and reconstruct the coding genome to obtain a comprehensive faba bean transcriptome atlas.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages of long-read sequencing, developing unified and practical approaches to analyzing the data remains a significant challenge. Previous studies applied standard Iso-seq bioinformatic pipelines to generate high-quality isoforms 34 , 35 . In the current study, we modified the standard pipeline by incorporating the Cogent tool 36 and the Cupcake ToFU package to refine and reconstruct the coding genome to obtain a comprehensive faba bean transcriptome atlas.…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of phenolic compounds, such as anthocyanin, observed in the previous study for the purple genotypes and their antioxidant activity are approximately 4~5 times higher than other cultivars caused by anthocyanin [ 14 ]. In the kenaf plant, the genes of phenylpropanoid biosynthetic enzymes, including HcPAL , Hc4CL , HcC4H , and HcCHS , have been isolated in previous studies [ 38 , 39 ]. Recent progress, including NGS technology, has facilitated various transcriptome analyses in kenaf.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, a hypothetical partial pathway of cellulose biosynthesis is presented in Fig. 9B (Kimura & Kondo, 2002;Huang et al, 2012;Lyu et al, 2020). Recently, analysis in A. thaliana revealed that AtCesA6-null mutants presented a reduced cell elongation of young seedlings with little effect on cell division, thus affecting the cellular integrity and biomass yield in mature plants (Hu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%